Biomechanic Variables and Volleyball Serve Receiving Skills: The Role of Special Exercises - Mohammed Khudhair Jawad; Ali Abdul Hassan Hussein; Nagham Salih Neama (Journal of Coaching and Sports Science, 2025)
Background of study: Volleyball is a highly dynamic sport in which serve reception plays a crucial role in determining a team's success. Ineffective serve reception can disrupt attack strategies. Therefore, developing training methods that improve reception accuracy and biomechanical efficiency is important.Aims and scope of paper: Preparing special exercises to aid in some biomechanical variables and learning to receive a volleyball serve for players. As well as identify the effect of these exercises on the variables under study.Methods: The experimental method was employed to address the research problem, utilizing a pre-test and post-test design with control and experimental groups. The samples comprised 20 players and were divided by a simple random method (lottery) into the experimental and control groups, each comprising 10 players.Result: The results showed that the significance level values were significant for all research variables, which indicates the significance of the differences between the pre-and-and post-test and in favour of the post-test. It was below the significance level (0.05).Conclusion: The exercises with the aids prepared by the researchers positively improved the values of the biomechanical variables (leg strength-maximum leg pressure-body angles-height, and speed of the ball at the moment of contact). Therefore, the researchers recommend using the exercises with the aids prepared by the researcher to learn and train serve-receiving skills in volleyball.